Metallic 1T phase MoS2 nanosheets for high-performance thermoelectric energy harvesting. (August 2016) - Huang, Huihui; Cui, Yue; Li, Qi; Dun, Chaochao; Zhou, Wei; Huang, Wenxiao; Chen, Lei; Hewitt, Corey A.; Carroll, David L.
Abstract: Thermoelectric materials that can generate electricity from waste heat will play an important role in the global sustainable energy solution. Low dimensional materials open new routes to high performance thermoelectric properties due to their unique density of states with confined electrons and holes. Here, we report that the phase engineered two dimensional transition metal dichalcogenides represent a new class of high performance thermoelectric materials. The organolithium chemically exfoliated nanosheets of MoS2 containing a high concentration of metallic 1T phase MoS2 show superior thermoelectric properties, with a room temperature power factor of 73.1 μW m −1  K −2, which is much higher than the pristine graphene or single wall carbon nanotubes can yield. Our first principle calculations on monolayer 1T phase MoS2 provide physical insight of their metallic and hole conductive nature, which happens to be important origins of their advantageous thermoelectric properties. These metallic 1T phase MoS2 nanosheets also reveal interesting moisture sensitive thermoelectric properties, indicating their potential diverse applications not only as thermoelectric energy harvesting devices but also as self-powered gas sensors. Graphical abstract: Highlights: Discovering the high thermoelectric properties of metallic 1T phase MoS2 nanosheets. Revealing the metallic and hole conductive mechanisms of 1T phase MoS2 . Discovering the moisture sensitive thermoelectric properties of 1T phase MoS2 . Discovering a whole new frontier of flexible thermoelectric materials.